Is it Possible to Provide Cash-Waqf Based Musyarakah Financing for Micro-Small Enterprises (MSEs) Business through Islamic Microfinance? - Wicaksono, Rianto Anugerah; Agustianto, Mochammad Andre (Management of Zakat and Waqf Journal (MAZAWA), 2024)
the development of asset waqf collection methods has moved to cash waqf collection. Islamic Microfinance, such as Baitul Mal Wa Tamwil (BMT) and Micro Waqf Bank, have tried to develop financing products based on cash waqf funds. The big question is how big is the risk of losing waqf funds due to financing scheme carried out by this Islamic Microfinance. In this research we try to develop a model to form of cash waqf-based musyarakah financing by providing suggestions for improvements, based on the literature and potential losses that arise from our simulation results. We use a dynamic simulation approach to obtain overall system behavior patterns in the next 5 years. The improvements that we propose include (1) Allocation of reserve impairment of non-performing financing, (2) Assistance and supervision efforts for financing, (3) evaluation of total waqf funds allocated for musyarakah financing, and (4) evaluation of the profit-sharing rate provided on Musyarakah Financing. Our final results show that Islamic Microfinance has the potential and feasibility to create a Cash-Waqf based Musyarakah Financing model, with several conditions, such as (1) being able to increase the ability to collect waqf gradually (2) allocating costs as an efforts to mitigate the risk of losing waqf funds using reserve impairment costs and financing supervision costs (3) optimizing the distribution of funds to the productive sector and (4) determine a profit-sharing ratio that is able to minimize the risk of loss of funds.